Analisis Dampak Pkl Terhadap Lalu Lintas Jalan Ki Hajar Dewantoro Kota Tegal - Malikha, Khotifatun; Yunus, Muhamad; Imron, Imron (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
This study was conducted to determine the impact of street vendors (PKL) on the capacity and performance of the road on Jalan Ki Hajar Dewantoro. This location was chosen due to problems arising from the existing road conditions. This study will use the MKJI 1997 method, in the form of geometric surveys and traffic volume surveys to determine road conditions. The survey will be conducted twice a week, namely on Tuesdays and Sundays. The survey will be conducted for 12 hours a day. In addition, the calculation of road capacity and performance also uses MKJI 1997, where the calculation results in a capacity value before the presence of street vendors of 2644.2 pcu/hour, while after the presence of street vendors the capacity value decreased to 1661.9 pcu/hour. This capacity value has experienced a significant decrease. Thus, it will affect the performance of Jalan Ki Hajar Dewantoro. This can be seen in the decrease in the level of service on the road section. From the calculation results, the value of the level of service decreased in the afternoon period, where the value of the level of service from A to B, this means that traffic conditions become denser.